Genotype distribution of T cell receptor β gene in Indonesian nasopharyngeal carcinoma patients (Medical Journal of Indonesia, 2011)
Background: Nasopharyngeal carcinoma (NPC) is a multifactorial genetic disease, characteristically endemic and shows considerable differences in its geographical distribution. Besides infection with EBV, genetic factors such as polymorphisms of TCR-β gene contribute to the incidence of NPC. This study investigates the association of TCR-β gene polymorphisms with individual susceptibility to develop NPC in Indonesian ethnic groups. Methods: The study was carried out by the PCR-RFLP method using Bgl II restriction enzyme to digest TCR-β gene. The PCR-RFLP analysis of TCR-β gene was used to determine allotypes of TCR-β gene in NPC patients and control among ethnic Chinese and indigenous groups in the population of Indonesia. Results: The results indicate that the distribution of TCR-β gene allotypes between NPC patients and controls are not signifi cantly different (p > 0.05); however, the frequency of A allele tends to increase in NPC patients. The distribution of TCR-β gene allotypes between Chinese ethnic group was not signifi cantly different from indigenous groups (p > 0.05). Conclusion: The distribution of TCR-β gene allele between NPC group and control groups showed no difference. The distribution of TCR-β gene between ethnic Chinese and indigenous groups showed no difference. Polymorphisms of TCR-βgene are not associated with NPC and ethnic groups in Indonesian population. (Med J Indones 2011; 20:171-7)